Alternative Facts and the ICER Proposed Policy on Access to Imaginary Pharmacoeconomic Worlds - Paul Langley (University of Minnesota Libraries Publishing, 2018)
The Institute for Clinical and Economic Review (ICER) announced at the end of March 2018 that it proposed to share executable draft economic models with relevant drug manufacturers during ICER evidence reviews. Taken at face value, ICER is offering manufacturers and other interested parties the possibility of a greater involvement in the assessment of modeled claims for product pricing. The purpose of this commentary is to point to the obvious limitations to this policy and to raise questions as to the extent to which ICER is willing to commit to transparency in the creation of modeled claims. While a commitment to greater transparency is to be welcomed, the fact remains that the ICER methodology does not meet the standards of normal science. ICER modeled claims not only lack credibility but are impossible to evaluate or replicate in treating environments. In proposing greater transparency ICER runs the risk of undermining its own credibility. If manufacturers have the opportunity to generate alternative models which create alternative claims, then ICER runs the risk of its pole position in health technology assessment being questioned. Rather than focused on non-evaluable lifetime modeled claims, there is the opportunity for ICER to reject its current business model, accepting instead a modelling paradigm that is consistent with the standards of normal science.   Type: Commentary